Rural, water and forest schools in the Covid-19 pandemic: difficulties and strategies in emergency remote teaching - Del Monaco, Graziela; Silva, Janaine Zdebski da; Correa, Antony Josue [UNESP]; Leite, Valter de Jesus (Univ Federal Norte Tocantins-ufnt, 2024)
This article investigated the difficulties faced by rural, water and forest schools, in different regions of the country, to guarantee access to basic education during the Covid-19 pandemic, as well as analyzing the pedagogical strategies used during emergency remote teaching, with emphasis on the use of social networks. The data were obtained through interinstitutional research entitled Education and rural schools in times of the Covid-19 pandemic, , developed between the years 2020-2023. National data were collected through an online questionnaire and interviews via video call. The subjects interviewed were workers from rural schools in 2020. The article uses quantitative data from questionnaires to profile the interviewees and qualitative data from interviews to highlight difficulties and strategies in school practice. Several difficulties in remote teaching were identified, with emphasis on the lack of internet and adequate equipment, compromising access to digital platforms. Other difficulties highlighted are related to the use of the printed materials strategy and the compromising of the teaching and learning process due to the need to carry out remote teaching. Notably, the social networks were used as a support strategy to facilitate teaching and learning.
Keywords: remote teaching; rural school; coronavirus pandemic